Local Wisdom Values From The Aspects Of Legal And Economic Norms In Traditional Wedding Ceremonials - Sujoko, Sujoko; Masni, Harbeng; Zahar, Erlina; Rahim, Arif; Hutabarat, Zuhri Saputra; Pratiwi, Heni; Rahima, Ade; Andriani, Lili; Tara, Firman; Afrila, Diliza; Pamungkas, Satriyo (LLDIKTI Wilayah 1 Sumatera Utara, 2024)
The purpose of this study is to describe the Values ??of Local Wisdom from the Aspect of Legal Norms and Customary Economy in the Wedding Ceremony Activities of the Air Haji Village Community, Pesisir Selatan Regency, West Sumatra Province. This study is included in the type of qualitative research using descriptive methods. The data in the primary data study are in the form of recordings of the wedding ceremonies of the Air Haji Village community, Pesisir Selatan, West Sumatra. Secondary data are in the form of interviews with traditional leaders. The data were analyzed using content analysis theory. The results of this study include three things, namely 1) the stage of activities before which must be carried out in the maresek wedding ceremony, manampiak bandua, maanta siriah, while those that do not have to be carried out are babako activities. 2) the stage of wedding day activities that must be carried out in the manjapuik marapulai wedding ceremony, akad nikah, basandiang di pelaminan, while those that do not have to be carried out are maanta marapulai activities. 3) the stage of activities after the wedding that must be carried out in the wedding ceremony, namely manjalang mintuo.